Strategi Kewirausahaan Sosial untuk Memberdayakan Perempuan Marginal : Kajian Literatur dan Implikasinya - Salwa Nasyifa; Rahayu Ramadhani; Istifarizah Amanah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This article discusses social entrepreneurship strategies in empowering marginalized women. Empowering marginalized women through social entrepreneurship is seen as a solution to address issues of gender inequality and poverty. Through a literature review, this research identifies various approaches and programs that have been implemented to enhance women's skills and knowledge, as well as their impact on their well-being. The results indicate that social entrepreneurship can increase economic independence and strengthen women's positions in society. This research concludes that support from various parties, including the government and private institutions, is crucial for the implementation of these strategies.